High Prevalence of HCV and Diabetes Mellitus in Multi-Transfused Subjects - Dipta, Tashmim Farhana; Hossain, Ahmed Zahid; Nazneen, Khadija (Ibrahim Medical College Journal, 2010)
The characteristics of the multitransfused patients remain unknown. They are exposed to chronic physiological and psychosocial stress. They bear the risk of many infectious diseases like malaria, hepatitis B and C, HIV etc. They are also exposed to chronic psychosocial stress that may lead to Type 2 diabetes mellitus (T2DM). This study was designed to address two important diseases in the multitransfused patients - hepatitis C virus (HCV), an infectious disease and T2DM, a noncommunicable but stress related one. The study was conducted in two tertiary care centers in Dhaka City. These centers have the standard facilities for blood transfusion. The study was conducted from July 2006 to July 2007. Detect-HCV (V.3), an Anti-HCV was used for detecting HCV while oral glucose tolerance test (OGTT) was done for diagnosing T2DM. The WHO criteria of 1997 for diagnosing T2DM and impaired glucose tolerance (IGT) were employed. A total of 125 multitransfused patients were investigated. Overall, the crude prevalence of HCV was 15%, T2DM was 28% and IGT was 13%. Of the diabetic subjects, 31.4% were positive for HCV and among the IGT subjects 12.5% were HCV positive. In contrast, of the total 74 non-DM and non-IGT subjects, only 8.1% were found to be positive for HCV. This study suggests that, the prevalence of diabetes mellitus and HCV are higher in multitransfused patients. This study also revealed that the prevalence of HCV is much higher in T2DM and IGT subjects than observed in non-DM, and non-IGT subjects. Further study is needed to determine other communicable and non-communicable diseases in the multitransfused population. Ibrahim Med. Coll. J. 2009; 3(2): 67-70 Key words: Multitransfused, HCV, Diabetes mellitus DOI: 10.3329/imcj.v3i2.4220